Variables that affect the sustainability of the pension system: the case of Ecuador for the period 1970-2023 - Ruiz Hinojosa, Daniela (2024)
This study used annual time series data from 1970 to 2023 to determine the variables that affect the Sustainability of the Ecuadorian Pension System. The following were considered as explanatory variables: the Sustainability Rate, Net Migration, Total Population, Global Participation Rate, Underemployment and Unemployment Rate, Life Expectancy at Birth, Fertility Rate, and Gross Domestic Product. The variable used to measure the Sustainability of the System was Pension Savings, resulting from the difference between the income and expenses received by the Ecuadorian Pension System. The most probable moments of structural changes were considered, which coincided with important events in the Ecuadorian economy, such as the year in which the country established the Official Dollarization Monetary System (2000) or radical government decisions regarding the pension system (2015). After applying the Lumsdaine and Papell (1997) approach, the stationarity of each series is examined, and it is concluded that applying the Autoregressive Distributed Lag Model (ARDL) was the best way to determine the relationships between the variables. In particular, the error correction version of the ARDL model was implemented to specify the short- and long-term determinants of pension savings in the presence of structural breaks. Thus, the results showed that, with the exception of the Gross Domestic Product, all the variables have a cointegration relationship, that is, pension savings were influenced by each of the indicators considered here.